2022
DOI: 10.1017/bca.2022.4
|View full text |Cite
|
Sign up to set email alerts
|

Early Education and Adult Health: Age 37 Impacts and Economic Benefits of the Child-Parent Center Preschool Program

Abstract: This article evaluates the long-term impacts of the Chicago Child-Parent Centers (CPC), a comprehensive early childhood program launched in the 1960s, on physical and mental health outcomes. This study follows a cohort of 1539 participants born in 1979–1980 and surveyed most recently at age 35–37 by employing a matched study design that included all 989 children who entered CPCs at ages 3 and 4 (1983-1985) and 550 comparison children of the same age from randomly selected schools participating in the usual dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…Focusing solely on the preschool component of CPC, Varshney et al. (2022) found that it produced savings between $1.35 and $3.66 at age 37. It is worth noting that these estimates were based only on health outcomes (i.e., diabetes, smoking and obesity), so it is possible that the programme may produce additional savings in other domains.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing solely on the preschool component of CPC, Varshney et al. (2022) found that it produced savings between $1.35 and $3.66 at age 37. It is worth noting that these estimates were based only on health outcomes (i.e., diabetes, smoking and obesity), so it is possible that the programme may produce additional savings in other domains.…”
Section: Resultsmentioning
confidence: 99%
“…When followed up at several points in their lives, participants were found to have significantly better outcomes than a group of similar individuals who had been randomised out of the programme: as adults, they had higher educational qualifications and earnings, improved health and health-related behaviours, and lower criminal activity, and these benefits have been found to last until age 54 (García, Heckman and Ronda, 2021). Similarly, long-term benefits were found for a number of other early childhood interventions targeted at very disadvantaged children, including the Jamaican Home Visit Program (Gertler et al, 2014), the Abecedarian Project (Campbell et al, 2012) and the Chicago Child-Parent Center Program (Ou, Yoo and Reynolds, 2021;Varshney, Temple and Reynolds, 2022).…”
Section: The Long-lasting Influence Of Early Childhoodmentioning
confidence: 98%
“…For example, some studies of pre-K programs find health benefits that by themselves exceed pre-K costs(Varshney et al, 2022).…”
mentioning
confidence: 99%